(untitled) (Sun’iy Intellekt Nazariyasi va Amaliyoti: Tajribalar, Muammolar va Istiqbollari, 2024)
This article discusses the problem of removing rain tracks from video. Although it is important to remove rain tracks from the image, there is not much research in this area and there are no reliable real-time algorithms. Difficulties in the rain trail removal algorithm are caused by the difficulty of seeing, low light, and the presence of a moving camera and objects. The problem facing the rain line restoration algorithm is to identify the rain lines and replace them with their original values for image processing. In this paper, we discuss the use of photometric and chromatic features for rain detection. An updated Gaussian mixture model (updated GMM) detected moving objects. This rain streak removal algorithm is used to detect rain streaks in videos and replace them with calculated values equal to the original value. Spatial and temporal features are used to replace rain lines with their original values.